KAJIAN PENERAPAN METODE LOGIKA FUZZY DALAM MENENTUKAN MAHASISWA TERBAIK - Saryoko, Andi (LPPM Universitas Nusa Mandiri, 2014)
College is constantly developing an academic climate in order to support the democratic process of learning who directs and being a graduate student best quality. Not just students expected, as science in the field but also to develop soft activity skills to be independent, graduates full of initiative, work, in a punctilious manner full responsibility and persistent. This capability student can get from 92 formally through Cocurricular, and academic curriculum extra and an extern Curricular. However, not all students willing and able to be a successful learner. A student with an unusually high academic utilizing to use his time in activities and extra Cocurricular Curricular. Contrarily active in the student organization Student Affairs and development activities soft skills did not obtain the value of academic high. It sometimes becomes influence or constraint student in achievement or in externalized his best be a student. In determining student best we can use methods fuzzy logic. By using the method fuzzy logic expected to determine the best student by using criteria such as final scores consisting of scores central semester (UTS), scores last semester (UAS), value absent / presence, duty and value quiz. Then aside from the final score we can make a judgment is parameters of the value of liveliness in the classroom the achievements and also organization participation in value. By using four final score, variable the liveliness and value achievement and value organization proceed with fuzzy logic methods have high accuracy in determining the best student.